Methodologies in Housing Research - N/A (The Urban International Press, 2005)
This book is a result of a conference organised by the Royal Institute of Technology (KTH) in collaboration with the International Association of People-Environment Studies (IAPS) and the European Network for Housing Research (ENHR) on the theme "Methodologies in Housing Research", held in Stockholm 22-24 September 2003. The conference was held under the umbrella of the IAPS Housing Network, coordinated by Prof. Roderick Lawrence, Geneva and Assoc Prof. Rolf Johansson, Stockholm. The selected articles of this conference were collected in this book in order to contribute to academic research on housing and architecture.
Foreword / Methodologies in contemporary housing research / Inquiry by Participatory Planning within Housing / On Case Study Methodology / Participant Observation - a Method for Inside Views / Evaluating Housing Projects by Paired Comparison in Multi-Method Case Studies / The ENABLE-AGE Project: Multi-Dimensional Methodology for European Housing Research / Comparative Case Studies in Cross-National Housing Research / Participatory Methods for Sustainable Remote Indigenous Housing in Western Australia / Consultation Methodologies for Improving Built Environment in Remote Aboriginal Communities / Socio-Spatial Analysis of Traditional Kuwaiti Houses / Methods for Understanding Children's Experience of the Physical Environment / Structural Analysis of Urban Space in Residential Areas / Empirical Analyses on Housing Vacancy and Urban Shrinkage / Researching Domestic Space and Income Generation in Developing Cities / Connecting Welfare State Regimes, Tenure Categories and Dwelling Type / Assessing the Environmental Efficiency of Buildings / Modelling Social Processes - A New Tool in the Field of Housing Research / Internet-Based Methodologies in Housing Research / Measuring Change in Housing Conditions Over Time / Measurement and Analysis of Less-Structured Data in Housing Research / Modelling Residential Quality Using Subjective and Objective Measures / Useful Concepts or Eternal Truths? Reflections on Case Study Generalization.
The book covers many academic research methods which can be used for housing research and architecture.
Keywords: Academic research, housing, research methods